Rhetorical Questions and Ruminations: Examining Early Career Faculty Experiences through Found Poetry - Willcox, Libba; McCormick, Kate (Art/Research International)

(untitled) (University of Alberta, 2021)
Transitioning from graduate student to early career faculty can often provoke uncertainty and questioning. This study explores the rhetorical and revealing nature of such questioning (i.e., Am I really this lost? Am I in the right place?). Utilizing methods from arts based research (Barone & Eisner, 2012), specifically poetic inquiry (Prendergast et al., 2009; Richardson, 1992), we created found poetry around rhetorical questions from our existing collaborative autoethnographic journal. We frame our findings with a selection of poems to provide insight into our lived experiences of transition. The question poems illustrate that our first year as assistant professors were preoccupied with managing tasks, balancing work, avoiding burnout, building relationships, and discovering how to belong in the new context. While rhetorical questions do not necessarily produce answers, questioning in a collaborative space allowed us to explore the struggle, complexity, and ambiguity of academic identity construction as early career faculty.